Pembelajaran Matematika Materi Pokok Kesebangunan Bangun Datar dengan Strategi Kokom Untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas 9 SMP Negeri 2 Sukodadi Lamongan - Moh. Maksum Sa’dullah (Departement of Mathematics Education, 2023)
This study aims to: (1) improve students' abilities in constructing their own concepts learned, (2) improve student learning outcomes in class 9 of SMP Negeri 2 Sukodadi on the subject matter of congruence flats. The subject of this research is class 9A students of SMP Negeri 2 Sukodadi Lamongan semester 2 academic year 2018/2019. This research is Classroom Action Research (PTK) which is carried out using 2 cycles and each cycle consists of 3 meetings. In the implementation of this learning, students always create conflicts through observing pictures and other mathematical objects. Meanwhile, to resolve cognitive conflicts, students try to find out from other learning materials/sources. The results of this classroom action research, (1) Learning with cognitive conflict strategies in each cycle and at each meeting for each aspect of observation shows significant positive changes; (2) the average score of student learning outcomes increased from 77.1 to 78.2; (3) the percentage of classical learning mastery students increased from 65.6% to 81.3%. In addition, those who like the way of teaching teachers with cognitive conflict strategies have also increased. These results indicate that through learning with the KoKom strategy, students are able to understand the concept of congruent shapes well and are able to apply it to solve problems related to congruent shapes